Local corruption and corporate cash holdings: Sheltering assets or agency conflict? - Xixiong Xu; Yaoqin Li (China Journal of Accounting Research, 2018)
This study investigates the impact of corruption on corporate cash holdings in China. The political extraction argument predicts that firms might shelter liquid assets to avoid extraction by corrupt officials. Using data on A-shared listed firms between 2007 and 2012, we find that firms located in more corrupt regions hold less cash, supporting this hypothesis. Political resources help to diminish the risk of exploitation, reducing the extent to which liquid assets are sheltered. We find that the negative association between corruption and cash holding is more significant for non-state-owned enterprises (Non-SOEs) than for state-owned enterprises (SOEs). Moreover, the cash holdings of Non-SOEs without political connections are more sensitive to corruption than those of Non-SOEs with political connections. These findings demonstrate that expropriation by corrupt officials is an important factor driving firms to manage liquidity.
Keywords: 650; Corruption; Corporate cash holding; Political extraction; Asset sheltering; Agency cost